2016
DOI: 10.1007/s11481-016-9651-3
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the COMT Val158Met Polymorphism in Major Depressive Disorder: Effect of Ethnicity

Abstract: The COMT (catechol-O-methyltransferase) Val158Met polymorphism (rs4680) is a potential susceptibility variant for major depressive disorder (MDD). Although many genetic studies have examined the association between MDD and this polymorphism, the results were inconclusive. In the present study, we conducted a series of meta-analyses of samples consisting of 2905 MDD cases and 2403 controls with the goal of determining whether this variant indeed has any effect on MDD. We revealed a significant association in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 90 publications
4
14
0
1
Order By: Relevance
“…As hypothesized, the COMT and BDNF had main and interaction effects on WM. The positive effect of the COMT Val allele on cognitive abilities is consistent with previous research with Asian samples (Qian et al, 2009; Yeh et al, 2009; Wang et al, 2016), but opposite of previous findings from Western samples that COMT -Met carriers showed better cognitive performance in both patients (Bilder et al, 2002; Joober et al, 2002) and healthy individuals (Caldú et al, 2007; Sheldrick et al, 2008). The main effect of BDNF on WM was modest, yielding no significant post hoc contrasts.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As hypothesized, the COMT and BDNF had main and interaction effects on WM. The positive effect of the COMT Val allele on cognitive abilities is consistent with previous research with Asian samples (Qian et al, 2009; Yeh et al, 2009; Wang et al, 2016), but opposite of previous findings from Western samples that COMT -Met carriers showed better cognitive performance in both patients (Bilder et al, 2002; Joober et al, 2002) and healthy individuals (Caldú et al, 2007; Sheldrick et al, 2008). The main effect of BDNF on WM was modest, yielding no significant post hoc contrasts.…”
Section: Discussionsupporting
confidence: 89%
“…Most studies that used Caucasian samples (Bruder et al, 2005; Aguilera et al, 2008) found that compared with the Val allele, the Met allele was correlated with better cognitive abilities, especially WM. On the other hand, in Asian samples, the Met allele was instead associated with higher incidence of major depressive disorder (MDD; Wang et al, 2016), lower IQ (Qian et al, 2009), lower scores on competency tests (Yeh et al, 2009), and lower WM (Wang et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“… showed in their study that the frequency of the Val allele among all healthy and depressed randomized European individuals was 51.42%. The allele frequency of COMT Val(108/158)Met, rs4680 genetic polymorphism is ethnicity‐dependent . Indeed, for the Asian ancestry, the Val allele had a frequency of 60.5% for the depressed population and 65.9% for the healthy population , whereas Hopkins et al .…”
Section: Discussionmentioning
confidence: 98%
“…60% of the metabolic degradation of dopamine (Karoum et al 1994), a neurotransmitter which plays a role in antidepressant action (Porcelli et al 2011). Moreover, Comt polymorphisms have been associated with depression (Koike et al 2018; Wang et al 2016) and response to antidepressants (Antypa et al 2013; O’Leary et al 2014). Adora1 encodes A 1 receptor, whose antagonism mediates caffeine-induced wakefulness (Fredholm et al 2016).…”
Section: Introductionmentioning
confidence: 99%